Chinese ESL learners' perceptual errors of English connected speech: Insights into listening comprehension. (June 2021) - Wong, Simpson W.L.; Leung, Vina W.H.; Tsui, Jenny K.Y.; Dealey, Jessica; Cheung, Anisa
Abstract: Comprehending native English connected speech is a daunting task for most non-native speakers (NNS) of English, who often misinterpret such input and result in poor listening comprehension in authentic situations. These misinterpretations of native English speech are critical to understanding the mechanisms underlying connected speech perception and the recovery strategies employed by NNS. In this study, we tested the perceptual errors of native English connected speech by 60 undergraduate learners of English as a second language (ESL) in Hong Kong and systematically classified their dictation responses. A total of 640 errors were identified and subsequently categorized into 9 main types and 20 subtypes of errors. The absolute number and relative frequency for each types and subtypes were reported. Our findings should inform teaching practices of Teaching English to Speakers of Other Languages (TESOL) educators and subsequently enhance the English connected speech listening comprehension skills of NNS.